Aluminum trichloride induces bone impairment through TGF-β1/Smad signaling pathway. (14th September 2016) - Sun, Xudong; Liu, Jianyu; Zhuang, Cuicui; Yang, Xu; Han, Yanfei; Shao, Bing; Song, Miao; Li, Yanfei; Zhu, Yanzhu
Abstract: Aluminum (Al) is recognized worldwide as serious inorganic contaminants. Exposure to Al is associated with low BMD and an increased risk of osteoporosis. However, the precise molecular mechanisms remains unclear. Thus, in this study, rats were orally exposed to 0 (control group, CG) and 0.4 g/L AlCl3 (AlCl3 treated group, AG) in drinking water for 120 days; osteoblasts were treated with AlCl3 (0.12 mg/mL) and/or TGF-β1 (4.5 ng/mL) for 24 h. We found that AlCl3 decreased the BMD, damaged femoral ultrastructure, decreased the activities of GSH-Px and SOD, and increased the levels of ROS and MDA in bone, decreased the activity of B-ALP and content of PINP, and increased the activity of TRACP-5b and content of NTX-I in serum, decreased mRNA expressions of TGF-β1, TβRI, TβRII and Smad4, protein expressions of TGF-β1, p-Smad2/3 and Smad2/3/4 complex, and increased Smad7 mRNA expression in bone and in osteoblasts. Moreover, we found exogenous TGF-β1 application reversed the inhibitory effect of AlCl3 on osteoblasts activity by activating the TGF-β1/Smad signaling pathway and increasing the mRNA expressions of ALP and Col I in osteoblasts. These results demonstrate that AlCl3 induces bone impairment through inactivation of TGF-β1/Smad signaling pathway.